Synthesis, characterization, and reactivity of Bispidine-Iron(IV)-Tosylimido species - Josephy, Thomas; Kumar, Ravi; Bleher, Katharina; Röhs, Fridolin; Glaser, Thorsten; Rajaraman, Gopalan; Comba, Peter (Inorganic chemistry, 2024)
Reported are the synthesis and detailed studies of the iron(IV)-tosylimido complexes of two isomeric pentadentate bispidine ligands (bispidines are 3,7-diazabicyclo[3.3.1]nonane derivatives). This completes a series of five tosylimido complexes with comparable pentadentate amine/pyridine ligands, where the corresponding [(L)FeIV═O]2+ oxidants have been studied in detail. The characterization of the two new complexes in solution (UV-vis-NIR, Mössbauer, HR-ESI-MS) shows that these oxidants have an intermediate spin (S = 1) electronic ground state. The reactivities have been studied as oxidants in C-H activation at 1,3-cyclohexadiene and nitrogen atom transfer to thioanisole. For the latter substrate, the entire set of data for the five ligands and for both nitrogen and oxygen atom transfer is now available and the interesting observation is that oxygen atom transfer is, as expected, generally faster than nitrogen atom transfer, with the exception of the two ligands that have four and three pyridine groups oriented parallel to the Fe-O and Fe-N axes. A thorough DFT analysis indicates that this is due to steric effects in the case of the [(L)FeIV═O]2+ species, which are less important in the [(L)FeIV═NTs]2+ compounds due to partial electron transfer from the thioanisole substrate to the iron(IV)-tosylimido oxidant.
Online veröffentlicht: 14. Juni 2024
Gesehen am 25.11.2024